Stability of general cognitive ability from infancy to adulthood: A combined twin and genomic investigation - Daniel E. Gustavson; Giulia A. Borriello; Mohini A. Karhadkar; Soo Hyun Rhee; Robin P. Corley; Sally-Ann Rhea; Lisabeth F. DiLalla; Sally J. Wadsworth; Naomi P. Friedman; Chandra A. Reynolds (Proceedings of the National Academy of Sciences, 2025)
Measures of general cognitive ability (GCA) are highly stable from adolescence onward, particularly at the level of genetic influences. In contrast, measurement of GCA in early life (before 3 y old) is less reliable and less is known about the stability of GCA across this period, including its relation to adult GCA. Using data from the Colorado Longitudinal Twin study (N = 1,098), we examined the stability of GCA measures across 5 time-points (years 1 to 2, 3, 7, 16, and 29), including how an array of cognitive measures given at 7 and 9 mo relate to later GCA. We then examined the genetic and environmental stability of GCA across the first 30 y of life using complementary methods: twin analyses and polygenic scores (PGSs). Two infant cognition measures, object novelty and tester-rated task orientation, predicted GCA in adulthood ( r = 0.16 and 0.18, respectively). Correlational analyses were consistent with a pattern of increasing stability across development for GCA measures between year 1 to 2 and adulthood ( r = 0.39 to 0.85). Subsequent twin analyses revealed that 22% of variance in adulthood GCA was captured by genetic influences on GCA from year 3 or earlier, with an additional 10% explained by shared environmental influences on GCA at year 1 to 2. PGSs for adulthood GCA and educational attainment predicted GCA from 1 to 2 y onward ( β s = 0.09 to 0.44) but not infant cognition. Findings suggest that genetic and environmental influences on GCA demonstrate considerable stability as early as age 3 y, but that measures of infant cognition are less predictive of later cognitive ability.